Optimizing Centralized Financial Management for MSMEs in the Mbulak Wilkel Tourism Area of Bantul with the Approaches of (Tri-N) Niteni, Nirokke, Nambahi, and Tri Pantangan - Suciani, Leni; Pitaloka, Dyah Ayu; Sari, Serly Faisa Nur Fatika; Rifaldi, Rifaldi; Setiawan, Miko; Sari, Pristin Prima (IJCS: International Journal of Community Service, 2024)
This study aims to optimize centralized financial management for MSMEs in the Mbulak Wilkel tourism area of Bantul through a local wisdom-based approach, specifically the concepts of "Niteni, Nirokke, Nambahi," along with the "Tri Pantangan" teachings of Ki Hadjar Dewantara. This community service program, involving students and faculty from Universitas Sarjanawiyata Tamansiswa, emphasizes a one-door cashier system to enhance financial efficiency and transparency. The methods employed include socialization, training, and the implementation of simple digital technologies such as MokaPOS to facilitate transaction recording. The results indicate that local-based approaches and community cooperation significantly encourage resident participation in more professional and effective centralized management.